Review of perforator flaps in head and neck cancer surgery. Issue 5 (October 2016) - Cho, Andrew; Hall, Francis T.
Abstract : Purpose of review: Perforator flaps are increasingly being used to reconstruct head and neck defects. They offer several advantages over nonperforator-based flaps with lower donor site morbidity and a versatile range of reconstructive options. The anterolateral thigh flap is well established in the head and neck and is a good example of a reliable perforator free flap. With the increasing use of both free and regional perforator-based flaps, it is timely to review their anatomy, clinical applications, and role in head and neck reconstruction. We also discuss increasingly popular perforator flaps such as the submental flap for the head and neck. Recent findings: The anterolateral thigh flap is now commonly used to reconstruct a wide variety of head and neck defects. The submental flap fills a niche role for reconstruction of intraoral defects. Summary: Perforator flaps are now mainstream reconstructive options in the head and neck surgeon's armamentarium.